First characterization of cultivable extremophile Chroococcidiopsis isolates from a solar panel - Baldanta, Sara; Arnal, Raquel; Blanco-Rivero, Amaya; Guevara, Govinda; Navarro Llorens, Juana María (Frontiers in Microbiology, 2023)
Microorganisms colonize a wide range of natural and artificial environments. Even though most of them are unculturable in laboratory conditions, some ecosystems are ideal niches for bioprospecting extremophiles with unique properties. Up today, there are few reports concerning microbial communities found on solar panels, a widespread, artificial, extreme habitat. Microorganisms found in this habitat belong to drought-, heat- and radiation-adapted genera, including fungi, bacteria, and cyanobacteria.This study presents the first identification and characterization of cultivable extremophile cyanobacteria from a solar panel in Valencia, Spain. The isolates are members of the genera Chroococcidiopsis, Leptolyngbya, Myxacorys, and Oculatella all genera with species commonly isolated from deserts and arid regions. Four of the isolates were selected, all of them Chroococcidiopsis, and characterized under different conditions of pH, salinity, temperature, and nitrogen and carbon sources. As extremophile cyanobacteria isolated from a dry and highly irradiated extreme environment, we also tested their UV-C and desiccation-resistance properties. Finally, gene transfer to these isolates was evaluated using SEVA plasmids with different replicons to assess their potential in biotechnological applications. Our results showed that all Chroococcidiopsis isolates chosen were resistant up to a year of desiccation, viable after exposition to high doses of UV-C, and capable of being transformed. Our findings revealed that a solar panel is a useful ecological niche in searching for extremophilic cyanobacteria to further study the desiccation and UV-tolerance mechanisms. We conclude that these cyanobacteria can be modified and exploited as candidates for biotechnological purposes, including astrobiology applications.